Lymphocyte migration in the micro-channel of splenic sheathed capillaries in Chinese soft-shelled turtles, Pelodiscus sinensis. (January 2016) - Zhang, Qian; Ullah, Shakeeb; Liu, Yi; Yang, Ping; Chen, Bing; Waqas, Yasir; Bao, Huijun; Hu, Lisi; Li, Quanfu; Chen, Qiusheng
Highlights: The sheathed capillary of the turtle spleen is a high endothelial venule-like vessel. It delineated the route of lymphocyte migration along the micro-channel. The micro-channel provides a structural basis for lymphocyte homing. Abstract: The structural characteristics of the splenic sheathed capillary were investigated using light microscopy and transmission electron microscopy (TEM). This study mainly focused on lymphocyte migration to the splenic white pulp via micro-channels in Chinese soft-shelled turtles, Pelodiscus sinensis . The results showed that the sheathed capillaries in the turtle spleen were high endothelial venule (HEV)-like vessels. These capillaries consist of micro-channels that facilitate lymphocyte migration to the splenic white pulp. The micro-channel is a dynamic structure comprising processes of endothelial cells, supporting cells, and ellipsoid-associated cells (EACs), which provides a microenvironment for lymphocyte migration. The pattern of lymphocyte migration in the micro-channel of the turtle spleen includes the following steps: (i) lymphocyte first adheres to the endothelium of the sheathed capillary, passes through the endothelial cells, and traverses through the basement membrane of the sheathed capillary; (ii) it then enters into the ellipsoid combined with supporting cells and EACs; and (iii) lymphocyte migrates from the ellipsoid to the periellipsoidal lymphatic sheath (PELS) via the micro-channel. This study provides morphological evidence for lymphocyte migration in the micro-channels of turtle spleens and also an insight into the mechanism of lymphocyte homing to the splenic white pulp of reptiles.